2012
DOI: 10.1590/s0034-89102012005000021
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco comportamentais acumulados para doenças cardiovasculares no sul do Brasil

Abstract: OBJECTIVE:To estimate the prevalence of, and identify factors associated with, accumulated risky behavior relating to cardiovascular diseases among adults. METHODS:This was a population-based cross-sectional study on a representative sample of 2732 adults of both sexes in Pelotas, Southern Brazil, in 2010. The behavioral risk factors investigated were: smoking; leisure-time physical inactivity; habitual consumption of visible fat in meat; and daily consumption of processed meats, red meat and whole milk. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
3
39

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 23 publications
4
24
3
39
Order By: Relevance
“…13 The agglomeration of cardiovascular risk factors and a high prevalence of cardiovascular risk factors was also observed in a large population-based study conducted in 16 Brazilian capitals. 14 Among the risk factors assessed, the sedentary lifestyle was the most frequent, with a similar distribution between men and women.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…13 The agglomeration of cardiovascular risk factors and a high prevalence of cardiovascular risk factors was also observed in a large population-based study conducted in 16 Brazilian capitals. 14 Among the risk factors assessed, the sedentary lifestyle was the most frequent, with a similar distribution between men and women.…”
Section: Resultsmentioning
confidence: 76%
“…This data was already recorded in a study conducted in the South of Brazil. 13 Although the level of physical activity has not yet been established as a risk factor in classic cardiovascular risk assessment scales, some studies have already established the potential for protection of physical activity against the risk of cardiovascular events. Data from the Multi-Ethnic Study of Atherosclerosis (MESA), concluded that higher levels of physical activity were associated with lower risks of atrial fibrillation.…”
Section: Resultsmentioning
confidence: 99%
“…23 Esses resultados são concordantes com os de estudos realizados em outros municípios. 27,28 A prevalência mais elevada de tabagismo entre os homens em piores condições econômicas reitera a situação descrita por Bastos e colaboradores 28 e expressa, em certa medida, as iniquidades mencionadas. Essa maior prevalência de tabagismo pode gerar maior carga de doenças entre os homens mais pobres Embora os resultados apontem as iniquidades sociais na ocorrência dos fatores estudados, o indicador selecionado permite apenas aproximação, pois, segundo Antunes, 29 a classificação ABEP, em sua concepção, não considerou as questões relacionadas à saúde e bem-estar social.…”
Section: Discussionunclassified
“…Resultado que se deve aos hábitos de vida, tais como consumo habitual de gordura, tabagismo, entre outros (15) . Quanto à faixa etária, 85% possuíam mais de 40 anos de idade, resultado semelhante ao encontrado entre trabalhadores de higiene e limpeza de um hospital universitário (16) .…”
Section: Estudounclassified